Dicopper(I) Complexes Incorporating Acetylide-Functionalized Pyridinyl-Based Ligands: Synthesis, Structural, and Photovoltaic Studies - Jayapal, Maharaja; Haque, Ashanul; Al-Busaidi, Idris J; Al-Rasbi, Nawal; Al-Suti, Mohammed K; Khan, Muhammad S; Al-Balushi, Rayya; Islam, Shahidul M; Xin, Chenghao; Wu, Wenjun; Wong, Wai-Yeung; Marken, Frank; et al. (Inorganic chemistry, 2018)
Heteroaryl incorporated acetylide-functionalized pyridinyl ligands (L1–L6) with the general formula Py-CC-Ar (Py = pyridine and Ar = thiophene-2-yl, 2,2′-bithiophene]-5-yl, 2,2′:5′,2″-terthiophene]-5-yl, thieno[2,3-b]thiophen-2-yl, quinoline-5-yl, benzo[c][1,2,5]thiadiazole-5-yl) have been synthesized by Pd(0)/Cu(I)-catalyzed cross-coupling reaction of 4-ethynylpyridine and the respective heteroaryl halide. Ligands L1–L6 were isolated in respectable yields and characterized by microanalysis, IR spectroscopy, 1H NMR spectroscopy, and ESI-MS mass spectrometry. A series of dinuclear Cu(I) complexes 1–10 have been synthesized by reacting L1–L6 with CuI and triphenylphosphine (PPh3) (R1) or with an anchored phosphine derivative, 4-(diphenylphosphino) benzoic acid (R2)/2-(diphenylphosphino)benzenesulfonic acid (R3), in a stoichiometric ratio. The complexes are soluble in common organic solvents and have been characterized by analytical, spectroscopic, and computational methods. Single-crystal X-ray structure analysis confirmed rhomboid dimeric structures for complexes 1, 2, 4, and 5, and a polymeric structure for 6. Complexes 1–6 showed oxidation potential responses close to 0.9 V vs Fc0/+, which were chemically irreversible and are likely to be associated with multiple steps and core oxidation. Preliminary photovoltaic (PV) results of these new materials indicated moderate power conversion efficiency (PCE) in the range of 0.15–1.56% in dye-sensitized solar cells (DSSCs). The highest PCE was achieved with complex 10 bearing the sulfonic acid anchoring functionality.